Pharmacy Students' Perspective on a Dual Degree PharmD/MPH Program at a Large Metropolitan School of Pharmacy - Holtzman CW; Sifontis NM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: To determine doctor of pharmacy (PharmD) students' perceptions of a PharmD and master of public health (MPH) dual degree program. Methods: A seven-item survey instrument was developed and distributed to students at a large metropolitan school of pharmacy during scheduled class time in April 2012. Results: Among the 611 students enrolled in the PharmD program, 447 (73%) responded. Of those who responded, 72.3% were either "very likely" or "likely" to consider enrolling in such a PharmD/MPH dual degree program, and 77.4% believed that it would be attractive to future students. The most commonly identified potential limitations to pursuing the dual degree were time commitment (19.9%), increased workload and stress (11.2%), and tuition cost (10.3%). The most notable advantages documented were increased job opportunities for public health-related pharmacy positions (26.9%), increased ability to serve patients and the community (13.4%), and increased marketability for future jobs (8.7%). Conclusions: PharmD student participants demonstrated overall positive attitudes and interest towards a PharmD/MPH dual degree program.